2019
DOI: 10.1111/inr.12559
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between emotional labour and job satisfaction in nursing

Abstract: Aim To investigate the relationship between emotional labour strategies and job satisfaction among nurses in Turkey. Background Nursing is one of the professions in which emotional labour is heavily used. The relationship between emotional labour strategies and job satisfaction has many different consequences in nursing. Introduction Although studies have focused on the relationship between emotional labour and job satisfaction among nurses abroad, no studies on the subject have been found in Turkey. Methods A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 33 publications
2
18
0
6
Order By: Relevance
“…The nurses' JS levels were high. This result is similar to the results of some studies in the literature 28 . In the literature, some studies reported different levels for nurses' job satisfaction 29–31 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The nurses' JS levels were high. This result is similar to the results of some studies in the literature 28 . In the literature, some studies reported different levels for nurses' job satisfaction 29–31 .…”
Section: Discussionsupporting
confidence: 90%
“…The job satisfaction levels of nurses working in inpatient clinics were lower than those of specialist inpatient nurses, and administrative nurses. Similarly, in the study by Gulsen and Ozmen, 28 nurse managers had higher JS than clinical nurses. Wu et al 35 stated that job satisfaction was related to the duties of nurses.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Therefore, job satisfaction should influence the emotional labour of bank employees, especially those bank employees that were acquired. Furthermore, job satisfaction is positively related to emotional labour, while emotional labour is negatively related to burnout ( Gulsen and Ozmen 2019 ; Grandey and Sayre, 2019 ). In the current study, the probable reason job satisfaction was not found to be a significant independent predictor of emotional labour is that the study was conducted during a crisis in the banking industry in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses are expected to show empathy, but, at the same time, detachment is identified as a trait of professionalism [ 14 ]. Using emotion management strategies makes it possible to satisfy one’s professional obligations [ 15 , 16 ]. However, while having good emotion management strategies protects the individual [ 17 ], emotion management in itself involves stress, which appears to justify detachment and emotional disengagement to overcome suffering in the workplace [ 10 ].…”
Section: Introductionmentioning
confidence: 99%